2003
DOI: 10.3109/03093640309167972
|View full text |Cite
|
Sign up to set email alerts
|

Social integration of juvenile amputees

Abstract: The objective was to assess the social integration of juvenile amputees according to marital status, schooling and occupation, and to compare it with the population of Asturias, Spain. A retrospective study was carried out of the juvenile amputees registered from 1976 to 1999 at the Prosthetics Unit of the Asturias Central Hospital (n = 281 amputees). The proportion of single women amongst the amputees was greater than in the population of Asturias (p < 0.05). Amongst the male amputees, relative to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…32,34 Even for those who successfully returned to work, most had to shift to different jobs or significantly reduce their working time, 30,32 which logically presents a financial impact. Fernandez et al 35 reported that men who had gone through an amputation early in life also tended to attain lower levels of education, contributing to a lower socioeconomic status. Clearly, limb loss is a life-changing event that inevitably affects a person's life experiences including educational achievement, financial outlook, and/ or other aspects of life.…”
Section: Discussionmentioning
confidence: 99%
“…32,34 Even for those who successfully returned to work, most had to shift to different jobs or significantly reduce their working time, 30,32 which logically presents a financial impact. Fernandez et al 35 reported that men who had gone through an amputation early in life also tended to attain lower levels of education, contributing to a lower socioeconomic status. Clearly, limb loss is a life-changing event that inevitably affects a person's life experiences including educational achievement, financial outlook, and/ or other aspects of life.…”
Section: Discussionmentioning
confidence: 99%